2014
DOI: 10.1177/0961203314524849
|View full text |Cite
|
Sign up to set email alerts
|

Costs of illness and quality of life in patients with systemic lupus erythematosus in South Korea

Abstract: The average total cost of illness was estimated to be KRW 9.82 million (US $ 8993) per year, of which 41.6% was accounted for by direct costs and 58.4% by indirect costs. In multivariate regression, patients with renal involvement and those with depression incurred an average increment in annual total costs of 37.6% (p = 0.050) and 49.1% (p = 0.024), respectively, and an average increment in annual direct costs of 26.4% (p = 0.050) and 43.3% (p = 0.002), respectively, compared with patients without renal invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
(44 reference statements)
2
16
0
1
Order By: Relevance
“…These findings were in agreement with a study done by Cho et al 33 and Medeiros et al 34 , they found that there was no significant difference in HRQoL between SLE patients with and without renal involvement.…”
Section: Resultssupporting
confidence: 93%
“…These findings were in agreement with a study done by Cho et al 33 and Medeiros et al 34 , they found that there was no significant difference in HRQoL between SLE patients with and without renal involvement.…”
Section: Resultssupporting
confidence: 93%
“…SLE is a source of disability that can create a burden of poor quality of life 6, 7, 8, 9, 10. The quality of life of SLE patients is always worse than that of healthy people and remains poor even in patients with SLE without complications and organ damage 6, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Tal constatação é preocupante, haja vista o tratamento do LES acarretar para o paciente alto custo financeiro (Cho et al, 2014;Panopalis et al, 2012;Xie et al, 2012).…”
Section: Discussionunclassified